(untitled) (Altre Modernità, 2022)
Based on prolonged apprenticeship with the indigenous Gente de Centro from Colombian Amazonia, this article discusses their research methodologies and the challenges they pose to ethnographic knowledge. Indigenous methodologies suggest that the modern disenchanted method, with its semi-structured interviews, focus groups, and data collection design, is inadequate to account for a world in which everything speaks and does so unexpectedly. Moreover, indigenous people’s warning to watch over the effects of knowledge means assuming responsibility towards the world that the act of knowing produces or could produce. In doing so, they underline the inseparability of epistemological, ethical, and political dimensions of research. Anthropology must respond adequately to such challenges if it is to contribute to indigenous cultural and political struggles and remain a credible approach to understanding the world. To do so, it must work against method as a data-gathering technique, and let itself be occupied by the cognitive practices of others.